Geoscience Literacy Profile of Junior High School Students - Desy Suryani; Eko Hariyono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The purpose of this research is to find out the geoscience literacy profile of junior high school students in Surabaya. The method used in this research is quantitative method. The test is done online through google form. The problem used in the test instrument is an adaptation of the TIMSS (Trends in Mathematics and Science Study) question in the Earth Science sub-discussion. The question instrument contains 10 points of multiple choice questions, and 3 items of description questions that are the result of the development of indicator slices of TIMSS (Trends in Mathematics and Science Study) 2019 and basic competency indicators of curriculum 2013. The study subjects were 85 respondents who were grade VIII students of State and Private Junior High in Surabaya. The results showed that the geoscience literacy capability profile of junior high school students in Surabaya with an average score of 58.2% is included in the low criteria, there are two indicators that have low achievement criteria, namely identifying or describing changes in the earth's surface, and the impact of geological events; and describe the process of hydrological cycles and know the sun as a source of energy for the hydrology cycle, sufficient achievement criteria, contained in the domain of cognitive knowing and reasoning. While the criteria for achievement are low, it is found in the cognitive domain applying